Implementacja metod łączenia modeli dyskryminacyjnych w programie R - Gatnar, Eugeniusz (The Implementation of Ensemble Methods in R, 2009)
Model aggregation is a well known technique used to improve the classification accuracy in many applications. In this paper, we review a number of available packages in the R environment that can be used for aggregation of classification models. We also compare the CPU time when procedures from different packages were applied. The comparison was done for five data sets from the UCI Repository. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 33-40